(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Flow cytometric study found that lymphoblasts of B acute lymphoblastic leukemia exhibited multiple aberrant antigens by which they can be distinguished from hematogones. These antigens are CD34 and CD123. Objective:To determine the immunophenotypic pattern of CD34 and CD123 expression in hematogone of reactive bone marrow and in neoplastic lymphoblast in B-acute lymphoblastic leukemia (ALL) patients and to evaluate the impact of that pattern in the residual disease detection after chemotherapy. Methods: This is a case control study to determine the expression of CD34 and CD123 in 30 patients newly diagnosed with B-ALL. Re-assessment was done for 20 patients of them after 4-6 weeks of chemotherapy; in addition to 10 patients with reactive bone marrow to assess hematogones. Results:In (93.4%) of the newly diagnosed B-ALL cases, leukemic blasts expressed both CD34 and CD123, Conversely, in (6.6%) cases, neither antigen was expressed. In hematogones; the immature hematogones (dim CD45, CD34 +) did not express CD123 while the mature hematogones (moderate CD45+, CD34-) expressed CD123. The strategy of concordant and discordant patterns of CD34/CD123 expression on B-ALL blasts and hematogones respectively in post chemotherapy patients remain stable. Conclusion:The distinct pattern of CD34 and CD123 expression on hematogones (discordant) and B-ALL blasts (concordant) is useful in correctly classifying immature B cells as residual leukemic blasts or hematogones in the bone marrow of patients treated for B-ALL. Keywords:B-Acute Lymphoblastic leukemia, Flow cytometry, Immunophenotypic aberrancy, Hematogones, CD34 and CD123.